Sistem Informasi Rawat Inap Berbasis Web Pada Klinik Medis Citra Husada - Wibisono, Muhammad Ario; Sutanto, Teguh; Soebijono, Tony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Citra Husada Medical Clinic is a premier medical clinic which also provides inpatient services. In this clinic has 2 floors with a capacity of 15 patients consisting of 8 room rooms and 7 chambers, where to register the hospitalization is done on the 1st floor and inpatient services on the 2nd floor. In the business process so far there are problems where the absence of information on the 1st floor administration of vacant rooms and to complete the administrative registration takes up to 20 minutes, the calculation of the cost of payment is still done manually causing the risk of mistakes and the time to complete up to 10 minutes, and still no detailed reporting to the management about the activities on the care in which the reporting is still limited to the written notes on the book by the administrative floor 2. Based on these problems, Citra Husada Medical Clinic requires inpatient information system to to reduce the time required to know the availability of empty rooms, accelerate the calculations performed ol eh the administration floor 2, and produce detailed reports to the management. The result of this research is inpatient information system which can show empty room and speed up administration registration to 9 minutes, accelerate the cost of hospitalization to 30 seconds and reduce the occurrence of errors in the calculation, and produce detailed reports to the management.